2021
DOI: 10.3390/children8050321
|View full text |Cite
|
Sign up to set email alerts
|

Lessons in Stories: Why Narrative Medicine Has a Role in Pediatric Palliative Care Training

Abstract: Narrative medicine is introduced and explored as a potential tool for developing competency in medical training, including reduction of burnout, sustaining empathy, and allowing for reflective practice. Developing cultural humility, communication skills, ethics, community building, and advocacy are also reviewed as domains that may be bolstered by training in narrative. Applications specific to pediatric palliative care are suggested, along with avenues for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the one hand, narrative theory educational learning can promote student empathy [4]. This may promote positive empathy among clinical staff by exploring literature [47]. Previous studies have shown [9,48] that medical professionals' participation in narrative medicine programs leads to increased self-reported empathy scores.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, narrative theory educational learning can promote student empathy [4]. This may promote positive empathy among clinical staff by exploring literature [47]. Previous studies have shown [9,48] that medical professionals' participation in narrative medicine programs leads to increased self-reported empathy scores.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative medicine-based education can significantly improve the humanistic qualities and empathy of doctors undergoing regular training, thereby improving their academic performance. Furthermore, narrative medicine-based education is often patient-centred and emphasizes humane patient conditions, which requires relieving and even eliminating the patients’ symptoms and pain and pursuing harmony and health [ 23 ]. Thus, narrative medicine-based education can improve individual residents’ medical and humanistic literacy and enhance doctor‒patient harmony [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…NM has been used mainly among adult clinicians and students within healthcare and medical education. There are examples of its application with children and adolescents (Lanocha, 2021;Ragusa et al, 2020), but we are not aware of instances specific to minors in a psychiatric context.…”
Section: Narrative Medicine (Nm)mentioning
confidence: 99%